An Approach to Citizenship Education That Includes Faith as an Integral Dimension - Sunderland, Chris (Journal of education & Christian belief, 2003)
This paper attempts to offer a way into Citizenship education based upon a philosophical and practical enquiry that acknowledges the importance of beliefs, values and commitments in every human society. It introduces four key conceptual tools, namely story, trust, power and success that together offer pupils and teachers an opportunity to explore the most fundamental human questions concerning knowledge, purpose and social systems. These concepts allow cross-curricular connection and a broad range of practical application that can meet the demands of the Citizenship curriculum.